Prevalence and associated factors of work-related musculoskeletal disorder symptoms amongst emergency medical service workers - Billy Chun Lung So; Eva Wing Fong Lee; Shamay Ng; Siu Shing Man (Scientific Reports)
Abstract Emergency medical service (EMS) plays a vital role in the healthcare system by delivering rapid response and acute care in critical situations. However, limited information exists regarding the prevalence and associated factors of work-related musculoskeletal disorder (WMSD) symptoms amongst EMS workers. This study aimed to examine the prevalence of WMSD symptoms and identify associated risk factors through a cross-sectional survey conducted in Hong Kong. A total of 404 EMS workers participated in the study. The overall prevalence of self-reported WMSD symptoms was 38.4%. Gender, exercise habits and years of work experience were significant predictors. In addition, several work-related tasks, such as standing, walking, sitting, balancing, twisting the body, gripping with fingers, lifting, pushing, hand control, wrist twisting and prolonged fixed hand movements, were positively associated with WMSD symptoms. These findings provided a strong foundation for developing targeted interventions to reduce WMSD risks and improve the health and well-being of EMS workers. The study also offered practical recommendations to help lower the prevalence of WMSDs in this essential workforce.